Runaway romances : Hollywood's postwar tour of Europe - Shandley, Robert R. (Philadelphia, PA : Temple Univ. Press, 2009)
Examines Hollywood's European travelogue romances from 1947 to 1964, the end of American isolationism and the advent of challenges in Hollywood that made American filmmakers begin filming abroad.
Hollywood's move abroad -- How Rome saved Hollywood -- Foreign affairs: metaphors of transatlantic relations -- Tourists with big cameras: widescreen runaways and class mobility -- Marrying the enemy: the occupation romance -- The end of the European romance.
Includes bibliographical references (pages 185-191), index and filmography (p. 173-183).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Motion picture industry -- United States -- History; Motion picture industry -- Production and direction -- United States -- History; Motion pictures, American -- Europe -- History; Love in motion pictures; Travel in motion pictures; Cinéma américain -- Europe -- Histoire; Amour au cinéma.; Voyage au cinéma.; Cinéma -- Industrie -- États-Unis -- Histoire; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; PERFORMING ARTS -- Film & Video -- History & Criticism; Love in motion pictures; Motion picture industry; Motion pictures, American; Travel in motion pictures; Europe; United States; Filmwirtschaft; Liebesfilm; Reise; Europa; USA; Travelogue romances; History